Plataforma Youtube® como ferramenta para o ensino de Biologia - Silva, Jane Margareth Brito (2019)
Holding students' attention in the classroom has been a difficult challenge faced by teachers. Against this reality, different pedagogical proposals are used in the classroom in order to change this history. The YouTube platform has been tested as a tool that could provide more attractive and encouraging lessons. It was hypothesized that students would approve the YouTube use as a tool that would make classes more attractive and that would motivate the search for knowledge. Therefore, this research had as general objective the evaluation of limits and possibilities of using this platform as a tool for Biology teaching. This study happened through the application of a structured didactic sequence in six moments with the theme Dengue. Its effectiveness was with a group of Biology students, from a High school class in the 11th Grade, of a public school located in Sorriso city - MT. It was a pedagogical intervention research with qualitative and descriptive approaches; active methodology and investigative approach were used. The data were obtained by a questionnaire application, with open and multiple-choice questions. In order to obtain the research results, the students answered the questionnaires applied in the first and in the last moment of the didactic sequence. The data collected through the questionnaires application and the students' involvement in the classes subsidized this research results. It was possible to verify that the use of YouTube platform promoted socialization, involvement, students’protagonism, greater incentive and motivation for the knowledge search. It has been expected that this study results can contribute to enrich other students’ knowledge and encourages teachers to use this pedagogical practice in the subjects they teach.